Trans-disciplinarity: The Singularities and Multiplicities of Architecture - Tahl Kaminer; Lukasz Stanek (Footprint)
This inaugural issue of Footprint aims at understanding today’s architecture culture as a negotiation between two antithetical definitions of architecture’s identity. The belief in the disciplinary singularity of architectural objects, irreducible to the conditions of their production, is confronted - in discourse and design - with the perception of architecture as an interdisciplinary mediation between multiple political, economic, social, technological and cultural factors. With the concept of trans-disciplinarity, the negotiation between these two positions is investigated here as an engine of the ‘tradition of the present’ of contemporary architecture - the discourses and designs which emerged in the 1960s and defined orientation points for today’s architectural thought and practice.